2017
DOI: 10.1093/mnras/stx2806
|View full text |Cite
|
Sign up to set email alerts
|

On the expected γ-ray emission from nearby flaring stars

Abstract: Stellar flares have been extensively studied in soft X-rays (SXR) by basically every X-ray mission. Hard X-ray (HXR) emission from stellar superflares, however, have only been detected from a handful of objects over the past years. One very extreme event was the superflare from the young M-dwarf DG CVn binary star system, which triggered Swift/BAT as if it was a γ-ray burst (GRB). In this work, we estimate the expected γ-ray emission from DG CVn and the most extreme stellar flares by extrapolating from solar f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…The integral fluxes averaged over each year's observation period are shown. M-Dwarf stars are characterized by flaring events which occur frequently with flare duration varying in time but for a total duration of ∼ 10 4 sec [3,4]. Very high energy γ-ray fluxes presented here demonstrate that these objects produce the flares of ∼ 10 33 − 10 35 ergs.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The integral fluxes averaged over each year's observation period are shown. M-Dwarf stars are characterized by flaring events which occur frequently with flare duration varying in time but for a total duration of ∼ 10 4 sec [3,4]. Very high energy γ-ray fluxes presented here demonstrate that these objects produce the flares of ∼ 10 33 − 10 35 ergs.…”
Section: Discussionmentioning
confidence: 69%
“…In the studies of flaring stars it was shown, that the frequency of flaring is uncertain [3,4], so to search for TeV γ-ray emission from these objects we chose objects that we have collected data from during different long-term observations. In accordance with the long-term program studying galactic γ-ray sources, more than ten-year-long observations of Tycho's SNR, Crab Nebula and Cyg X-3, are being carried out in the SHALON experiment [8,9].…”
Section: Observations Of Red Dwarfsmentioning
confidence: 99%
“…Even if our models take only the IC halo component into account, this component should be dominant in super-luminous stars. However, the possibility of enhanced 𝛾-ray flux due to massive stellar flares is also appealing (Ohm & Hoischen 2018). For the Sun, some massive flares emit more 𝛾-rays within one hour than the whole solar disk in one year (Abdo et al 2011;Ackermann et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These stars produce powerful stellar flares, which sometimes occur several times per day, but its flare frequency is uncertain. The total energy release estimates as 10 34 − 10 36 ergs [1,2]. The total energy of cosmic rays produced by the dwarf star flares in the Galaxy is estimated as ≈ 10 51 − 10 53 ergs [3].…”
Section: On Red Dwarf Starsmentioning
confidence: 99%